DASH-2: Flexible, Low-Cost, and High-Throughput SNP Genotyping by Dynamic Allele-Specific Hybridization on Membrane Arrays - Jobs, Magnus; Howell, W. Mathias; Strömqvist, Linda; Mayr, Torsten; Brookes, Anthony J. (Genome Research, 2003)
Genotyping technologies need to be continually improved in terms of their flexibility, cost-efficiency, and throughput, to push forward genome variation analysis. To this end, we have leveraged the inherent simplicity of dynamic allele-specific hybridization (DASH) and coupled it to recent innovations of centrifugal arrays and iFRET. We have thereby created a new genotyping platform we term DASH-2, which we demonstrate and evaluate in this report. The system is highly flexible in many ways (any plate format, PCR multiplexing, serial and parallel array processing, spectral-multiplexing of hybridization probes), thus supporting a wide range of application scales and objectives. Precision is demonstrated to be in the range 99.8–100%, and assay costs are 0.05 USD or less per genotype assignment. DASH-2 thus provides a powerful new alternative for genotyping practice, which can be used without the need for expensive robotics support.
10.1101/gr.801103